Colorectal Cancer Screening: Tests, Strategies, and Perspectives - Stracci, Fabrizio; Zorzi, Manuel; Grazzini, Grazia (Frontiers in Public Health, 2014)
Screening has a central role in colorectal cancer (CRC) control. Different screening tests are effective in reducing CRC-specific mortality. Influence on cancer incidence depends on test sensitivity for pre-malignant lesions, ranging from almost no influence for guaiac-based fecal occult blood testing (gFOBT) to an estimated reduction of 66–90% for colonoscopy. Screening tests detect lesions indirectly in the stool [gFOBT, fecal immunochemical testing (FIT), and fecal DNA] or directly by colonic inspection [flexible sigmoidoscopy, colonoscopy, CT colonography (CTC), and capsule endoscopy]. CRC screening is cost-effective compared to no screening but no screening strategy is clearly better than the others. Stool tests are the most widely used in worldwide screening interventions. FIT will soon replace gFOBT. The use of colonoscopy as a screening test is increasing and this strategy has superseded all alternatives in the US and Germany. Despite its undisputed importance, CRC screening is under-used and participation rarely reaches 70% of target population. Strategies to increase participation include ensuring recommendation by physicians, introducing organized screening and developing new, more acceptable tests. Available evidence for DNA fecal testing, CTC, and capsule endoscopy is reviewed.